Reovirus type-2–triggered autoimmune cholangitis in extrahepatic bile ducts of weanling DBA/1J mice - Nakashima, Tomomi; Hayashi, Toshiharu; Tomoeda, Saki; Yoshino, Midori; Mizuno, Takuya (Pediatric research, 2014)
Background: Reovirus is a proposed cause of infantile biliary atresia. However, mechanistic insight regarding Reo-2 as a potential cholangiotropic virus is lacking. Furthermore, it is unknown whether Reo-2 infection can induce autoimmune-mediated bile duct injury. Methods: Lesions of bile ducts in newborn DBA/1J mice infected with Reo-2 were analyzed immunopathologically. Results: Damage to biliary epithelia occurs after Reo-2 infection. In addition, nonsuppurative cholangitis with fibrosis in extrahepatic (especially septal) bile ducts developed following complete viral clearance from the liver. At the inflamed ducts, major histocompatibility complex class I expressing (+) and FAS + cholangiocytes were associated with FAS ligand + lymphocytes and tumor necrosis factor-α + mononuclear cells (macrophages and lymphocytes). These cholangiocytes were apoptotic and necrotic. Moreover, affected ducts were infiltrated by CD3 + , CD4 + , CD8 + , IFN-γ + , and FAS + lymphocytes. Analysis of blood from Reo-2–infected mice revealed that they developed anticholangiocyte cytoplasm antibodies and had high serum IFN-γ concentration. Notably, there was no increase in Foxp3 + lymphocytes at inflamed ducts, lymph nodes, and thymi. Conclusion: Reo-2 infection induced T-helper cell type 1–dependent injury to bile ducts in weanling mice. The lesions observed in mice may be analogous to those associated with human infantile biliary atresia, which are caused by an autoimmune-mediated process.